"Green" Catalyst for the Oxygen Reduction Reaction in Metal-Air Systems with Aqueous Electrolyte. Issue 11 (6th July 2020) - Popov, Iliyan; Banov, Krum; Milusheva, Yovka; Boukoureshtlieva, Reneta; Stankulov, Toma; Petkov, Todor; Vidakovic-Koch, Tanja; Banov, Branimir
Abstract : Thermally treated caffeine doped active carbon (Caffeine-Norit) is studied as a catalyst for the oxygen reduction reaction (ORR) with application in metal-air systems with neutral aqueous electrolytes. Catalytic activity is characterized by polarization curves and Tafel plots and the results are compared with 5% Platinum (5% Pt-Norit) and 4% Silver (4% Ag-Norit) catalysts. The Tafel slopes of all three catalysts are equal, the activity of Ag-Norit being somewhat lower then both Caffeine-Norit and Pt-Norit. The polarization curves are also comparable, especially in the low current density region. The increase of overpotential for the Caffeine-Norit at current density higher than 50 mA cm −2 is due to accumulation of H2 O2 in the catalyst layer. This was demonstrated by a simple method for detection of peroxides in neutral electrolytes based on indigo carmine indicator. The discharge curves of Caffeine-Norit in 4 M NaCl electrolyte at 10 mA cm −2 display a plateau at potential of −320 mV vs Ag/AgCl (1.23 V vs MA8M magnesium alloy).